Create a costume! - Myer, Sarah (Maker comics., 2019)
Uses a story in graphic-novel format about friends Bea and Parker who love comics and want to attend a comics convention in costume. They learn step-by-step from Costume Critter how to do research, create eleven budget-friendly costumes, and troubleshoot problems.